Practicality test of HOTS-based worksheet on evolution topic for high school students - Nurhidaya Nurhidaya; Adnan Adnan; Abd. Muis (Jurnal Biolokus, 2023)
Initial studies on the use of high school student’s worksheets based on higher order thinking skills (HOTS) in learning biology showed that HOTS content in the worksheet used by teachers is still low. Based on this, HOTS-based worksheet on evolution material has been developed. The type of research is a development research by using ADDIE model. The practicality test of HOTS-based worksheet was carried out at SMA Negeri 4 Wajo, South Sulawesi in March 2022, with 2 biology teachers and 30 students of grade 12th. The data collected through some instruments such as the observation sheet for the implementation of the worksheet and the questionnaire for students and teacher’s response. The criteria for HOTS-based worksheet are declared practical if the minimum value of the percentage of product implementation obtained is 71.00%, and the average percentage of respondents through questionnaires is ≥70.00%. Generally, product implementation through the observation sheet was 84.46% (very well implemented category); teacher responses to the practicality of the worksheet was 85.83% (very positive response category); and student responses was 85.94% (very positive response category). Refer to the research results, it can be concluded that the worksheet has met the practical criteria.